Desain Informasi Ikigai Sebagai Nilai Hidup Bangsa Jepang Melalui Media E-book - Bela, Bela; Persada, Satria Indra Praja (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2022)
Besides being known as a country with a highly dedicated population, Japan is also known to have a high life expectancy because it holds a life value called ikigai. Ikigai is a concept of Japanese thought that can explain the pleasures and meaning of life through small things. Some urban communities, especially the city of Bandung, are known to still recognize ikigai as a western modified diagram which is not the true meaning of ikigai for the Japanese because for the Japanese, ikigai does not always have to be related to work and income, but not a few also do not know ikigai. at all. With these problems, a design is needed to inform the true meaning of ikigai for the Japanese. The purpose of this design is to clear up misunderstandings related to ikigai which is described as a diagram and to tell the true meaning of ikigai for the Japanese as an alternative and new insight so that the design solution is to make an information design through an e-book. With the existence of this e-book, it is hoped that it will enable the public to obtain information about ikigai in a practical and easily accessible manner in accordance with the current lifestyle of the audience.